MOTIVASI KERJA DALAM PENGEMBANGAN USAHA PERSPEKTIF EKONOMI ISLAM (STUDI PADA WARALABA KEBAB TURKI BABA RAFI DI SURABAYA) - Saifuddin Saifuddin (Nurul Jadid University, 2019)
Kebab Turki Baba Rafi franchise is one of the pioneers of kebab food in Indonesia, one of the worldwide local franchisees, and a work motivation that aspires to be the largest franchise in the world. Kebab Turki Baba Rafi has made a major contribution to the economy in Indonesia, by implementing a precise development strategy. Work motivation plays an important role in developing business in Kebab Turki Baba Rafi. This motivation is what makes the success of Kebab Turki Baba Rafi to successfully penetrate the international market. This study aims to reveal and analyze: (1) what work motivation is applied in Kebab Turki Baba Rafi (2) contributions made, and (3) its development strategy, the approach used in this research is descriptive qualitative research with survey research methods . Data collection is done by interview, observation and documentation. Data analysis techniques using the theory of Miles and Huberman which is done in three steps, namely: data reduction, data presentation, and conclusions. The checking of the validity of the data is done by: (1) checking the methodology used, (2) correcting the results of the research report, (3) triangulating sources and methods. The results of the study found several factors of work motivation that were applied including: (1) achievement, namely giving a bonus if it exceeded the sales target, (2) responsibility, namely decisive in enforcing regulations and punishing those who made mistakes, (3) development, namely providing guidance in every religion once a month. (4) administrative policy, namely providing direction using good and polite speech, (5) interpersonal relationships that are mutually supportive, (6) working conditions namely providing comfort and complete work facilities. His contribution provides extensive employment, creating professional expertise. Whereas in its development strategy applying the Prophet's business style which includes Shiddiq, Amanah, Tabligh, and Fatanah